(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we pay attention to the number of limit cycles for a class of piecewise smooth near-Hamiltonian systems. By using the expression of the first order Melnikov function and some known results about Chebyshev systems, we study upper bound of the number of limit cycles in Hopf bifurcation and Poincaré bifurcation respectively.